A unique mitochondrial gene bock inversion in Antarctic Trematomin fishes: A cautionary tale - Patel, S.; Evans, C. W.; Stuckey, A.; Matzke, N. J.; Millar, C. D. (Zenodo, 2023)
Many Antarctic notothenioid fishes have major rearrangements in their mitochondrial (mt) genomes. Here we report the complete mt genomes of three trematomin notothenioids: the bald notothen ( Trematomus ( Pagothenia ) borchgrevinki ); the spotted notothen ( T. nicolai ); and the emerald notothen ( T. bernacchii ). The three mt genomes were sequenced using next-generation Illumina technology, and the assemblies verified by Sanger sequencing. When compared with the canonical mt gene order of the Antarctic silverfish ( Pleuragramma antarctica ), we found a large gene inversion in the three trematomin mt genomes that included tRNA Ile , ND1, tRNA Leu2 , 16S, tRNA Val , 12S, tRNA Phe and the control region. The trematomin mt genomes contained three intergenic spacers, which are thought to be the remnants of previous gene and control region duplications. All control regions included the characteristic conserved regulatory sequence motifs. Although next-generation DNA sequencing technology has allowed the rapid and cost-effective sequencing of a large number of complete mt genomes, it is essential in all cases to verify the assembly in order to prevent the publication and use of erroneous data. Data includes fourteen fastq files and one md5 file detailed in the accompanying README. Funding provided by: University of Auckland Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100001537 Award Number: N/A Funding provided by: Allan Wilson Centre for Molecular Ecology and Evolution Crossref Funder Registry ID: http://dx.doi.org/10.13039/100007610 Award Number: N/A